Gaya Pendidikan Rasulullah SAW dalam Psikoterapi Islam - Muhamad Firdaus Bin Alias (An-Nuha, 2023)
Psychotherapy is a field of psychology that aims to solve human or mental health problems. When it comes to defining mental health, it is separated into two categories: negative patterns and positive patterns. The negative pattern is a person's avoidance of all mental diseases. While the second pattern is a positive one, it refers to an individual's ability to adapt to their social environments (Mahmud 1984), such as mental tension, anxiety, mental disorders, emotional stress, depression, phobias, neurosis, psychopathology, psychosis, and others that are influenced by various factors. Individual qualities, the environment, and life events all have an impact on a person's mental health. Self-esteem, temperament, and coping abilities are examples of individual qualities. The development of Islamic education during the time of Rasulullah SAW is the subject of this study, which incorporates a qualitative approach, a content analytic technique, and a topical emphasis.